Age, gender and socioeconomic patterns of awareness and usage of e-cigarettes across selected WHO region countries: evidence from the Global Adult Tobacco Survey. Issue 1 (19th January 2023) - Kundu, Sampurna; Shaw, Subhojit; Khan, Junaid; Chattopadhyay, Aparajita; Baptista, Emerson Augusto; Paswan, Balram
Abstract : Objectives: The study explores the awareness and e-cigarette use by demographic and socio-economic characteristics of selected 14 Global Adult Tobacco Survey (GATS) countries. Design: Cross-sectional. Setting: 14 countries. Participants: Surveyed population ≥15 years selected through multi-stage cluster sampling. Primary and secondary outcome measures: We selected 14 countries from 6 different WHO regions where GATS was conducted in different years during 2011–2017. Results: Awareness and usage of e-cigarette were highest in Greece and lowest in India. Females were less aware of e-cigarette across ages. The gender gap in awareness is wide in Greece post 50 years of age, while the gap is distinct in early ages in Kazakhstan and Qatar. The gender difference in use of e-cigarette was negligible in most of the countries except among the younger cohorts of Russia, Philippines Malaysia and Indonesia. Relatively higher prevalence of e-cigarette smoking among females in the older adult age was observed in some of the Asian countries like India. Multivariate analysis indicates that those who were younger, male, residing in urban areas, current tobacco smokers were more likely to use e-cigarette than their counterparts. Though prevalence of e-cigarette use increased with wealth and education, such pattern is not strong and consistent. Promotional advertisement plays important role in higher use of e-cigaratte. The predicted national prevalence of e-ciragette use was highest in Malaysia . Conclusions: E-cigarette use is more among urban adults, current smokers, males and in countries with promotional advertisement of e-cigarette. Area specific interventions are needed to understand the nature of e-cigarette use. Russia, Ukraine, Costa Rica and Mexico need better understanding to explore whether e-cigaratte use is an indulgence to new mode of addiction, as youth being highly likely to adopt this practice.